Translation and the Unspeakable: Ricoeur, Otherness, and Interdisciplinarity - Godin, Mark (Literature and theology, 2013)
Paul Ricoeur's interest in the philosophy of translation led him to describe the space of meeting and openness to the textual worlds of other languages as ‘linguistic hospitality'; he proposed this as a model for generating other types of constructive meetings of distinct groups. This paper suggests that interdisciplinary work can be constructed following the lines of this ‘linguistic hospitality', exploring Ricoeur's philosophy of translation for what it might teach about engaging in interdisciplinarity, arguing that Ricoeur's constant assertion that boundaries not be effaced is especially helpful for reminding us that interdisciplinarity requires the recognition of otherness.